Pengaruh Retailing Mix Terhadap Keputusan Pembelian - Uliana Muslimin (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
This research aims to find out the influence of Retailing Mix indicators (products, prices, locations, services, promotions, and store atmosphere) on purchasing decisions at Alfamart in Jalan Andi Makkasu Pinrang Regency. This study takes the population as consumers who have made purchases at the mini-market Andi Makkasau. The sampling technique used in this study is accidental. Sampling with axial or accidental sampling technique is a technique of determining samples based on chance or anyone who meets with researchers can be used as a sample, and if the person encountered is seen as suitable as a source of data. This study was conducted from April to May 2020 using SPPS 2.1. The results showed that the product-free variables, prices, locations, services, promotions, and store atmosphere (simultaneously) had a positive and significant effect on the bound variables (purchasing decisions), this is evidenced by the results of statistics Fhitung of 119,389 results of determinant test R2 in this study obtained determinant value R2 of 0.889 which means explaining the magnitude of the influence of the product, price, location, service, Promotion, and Store Atmosphere towards Purchase Decision is 88.9% and the remaining 11.1% explained other variables.